Systemic lupus erythematosus: alertness in the practice of a dermatologist - M. M. Tlish; Zh. Yu. Naatyzh; T. G. Kuznetsova; E. A. Chernenko (Лечащий Врач, 2021)
Systemic lupus erythematosus (SLE) is an autoimmune disease, the etiology of which remains unknown. Skin syndrome in SLE is often of paramount diagnostic value – skin lesion is the earliest symptom in 20-30% of cases, and in 60-70% it manifests itself at various stages of the course of the disease, which leads to the patient's primary referral to a dermatologist. Frequent diagnostic errors are due to the absence of clinical symptoms of systemic lesions in the presence of cutaneous manifestations of lupus erythematosus (LE). In this case, laboratory tests are an integral part of the algorithm for managing patients with LE at the stage of contacting a dermatologist. The most specific laboratory test is the determination of antinuclear antibodies by an indirect immunofluorescence reaction, referred to as antinuclear factor (ANF). An elevated ANF titer is included in the list of diagnostic criteria for SLE, its detection allows one to suggest a diagnosis of SLE and determine a further algorithm for the provision of medical care. The article presents two clinical cases illustrating that against the background of an isolated skin lesion and the absence of visible somatic pathology, abnormalities in immunological tests were identified. This made it possible to suspect the systemic course of the process at an early stage and refer patients to a rheumatologist's consultation, where the diagnosis of SLE was confirmed.